Age and obesity alter the relationship between femoral articular cartilage thickness and ambulatory loads in individuals without osteoarthritis. Issue 3 (26th November 2013) - Blazek, Katerina; Favre, Julien; Asay, Jessica; Erhart‐Hledik, Jennifer; Andriacchi, Thomas
ABSTRACT Articular cartilage is sensitive to mechanical loading, so increased risk of osteoarthritis in older or obese individuals may be linked to changes in the relationship between cartilage properties and extrinsic joint loads. A positive relationship has been reported between ambulatory loads and cartilage thickness in young individuals, but whether this relationship exists in individuals who are older or obese is unknown. This study examined the relationship between femoral cartilage thickness and load, measured by weight × height and the peak adduction moment, in young normal‐weight (28 subjects, age: 28.0 ± 3.8 years, BMI: 21.9 ± 1.9 kg/m2), middle‐aged normal‐weight (27 subjects, 47.0 ± 6.5 years, 22.7 ± 1.7 kg/m2), young overweight/obese (27 subjects, 28.4 ± 3.6 years, 33.3 ± 4.6 kg/m2), and middle‐aged overweight/obese (27 subjects, 45.8 ± 7.2 years, 31.9 ± 4.4 kg/m2) individuals. On the lateral condyle, cartilage thickness was positively correlated with weight × height for all groups (R2 = 0.26–0.20) except the middle‐aged overweight/obese. On the medial condyle, weight × height was significantly correlated only in young normal‐weight subjects (R2 = 0.19), as was the case for the correlation between adduction moment and medial–lateral thickness ratio (R2 = 0.20). These results suggest that aging and obesity are both associated with a loss of the positive relationship between cartilage thickness and ambulatory loads, and that the relationship is dependent on the compartment and whether the load is generated by body size or subject‐specific gait mechanics. © 2013 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 32:394–402, 2014.